REVIEWS. (4th March 2011) - Jennings, Matt; Brocklehurst, Robert John; Wood, Nigel; Haddow, Sam; Pattie, David; Hauthal, Janine; Chow, Broderick D.V.
COMMUNITY POLITICS AND THE PEACE PROCESS IN CONTEMPORARY NORTHERN IRISH DRAMA, EVA URBAN, (2010) Oxford, Frankfurt am Main, Bern and New York: Peter Lang International Academic Publishers, 303 pp., ISBN: 978-3-0343-0143-5, pbk, £38.00GET REAL: DOCUMENTARY THEATRE PAST AND PRESENT, ALISON FORSYTH AND CHRIS MEGSON (EDS), ([2009] 2011) Basingstoke: Palgrave Macmillan, 264 pp., ISBN: 0-230-22115-7, hbk, £52.00; ISBN: 0-230-33689-2, pbk, £17.99THEATRE: THE REDISCOVERY OF STYLE, MICHEL SAINT-DENIS, (2009) Jane Baldwin (ed.), London and New York: Routledge Theatre Classics, 202 pp., ISBN: 978-0-415-45048-5, pbk, £17.99DISASTER CAPITALISM; OR MONEY CAN'T BUY YOU LOVE, RICK MITCHELL, (2011) Bristol: Intellect, 299 pp., ISBN 978-1-84150-430-8, pbk, £14.95THEATRE AND ETHICS, NICHOLAS RIDOUT, (2009) London: Palgrave, 78 pp., ISBN 978-0-230-23027-1, pbk, £4.99DAS DRAMA DES PREKÄREN: ÜBER DIE WIEDERKEHR DER ETHIK IN THEATER UND PERFORMANCE, KATHARINA PEWNY, (2011) Bielefeld: transcript, 336 pp., ISBN 978-3-8376-1651-4, pbk, €32.80THE TRANSFORMATIVE POWER OF PERFORMANCE (TRANS. SASKYA IRIS JAIN), ERIKA FISCHER-LICHTE, (2008) Abingdon: Routledge, 232 pp., ISBN: 978-0-415-45856-6, pbk, £22.99